Parallelized computational electromagnetics TLM algorithms on NVIDIA graphics processing units - Rossi, F.; So, P. (2009 IEEE Pacific Rim Conference on Communications, Computers and Signal Processing, 2009)
Advances in computing technology have brought parallel processing power to desktop and laptop computers. As multi-core processor technology becomes mature, a new front in parallel computing technology based on graphics processors has emerged. This paper reports two transmission line matrix algorithms for the latest NVIDIA graphics processors.